Mewujudkan Tata Kelola Pemerintahan yang Baik di Indonesia: Kajian Teoretis atas Prinsip, Tantangan dan Strategi Implementasi - Hari Suriadi (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2025)
Good governance is a fundamental principle in building a public administration system that is accountable, transparent, and participatory. In Indonesia, various regulations and policies have adopted the principles of good governance, yet significant gaps remain between conceptual ideals and practical implementation. This article aims to conceptually analyze the dynamics, challenges, and reform directions of governance in Indonesia. Using a qualitative approach through a descriptive-analytical literature review, this study examines both classical and contemporary theories of good governance and evaluates Indonesia's governance practices over the past two decades. The findings indicate that policy inconsistency between central and local governments, low bureaucratic integrity, weak oversight systems, and limited public participation are major obstacles to realizing ideal governance. This article proposes five reform strategies: strengthening political and institutional leadership, inclusive digital transformation, civil society empowerment, bureaucratic ethics internalization, and multi-actor collaboration in governance ecosystems. This study offers a theoretical contribution to the discourse of public administration and provides policy directions to enhance governance quality in Indonesia.